DEVELOPMENT OF SUSTAINABLE AGROTOURISM BASED ON SOCIAL CAPITAL IN TOURISM-AWARE COMMUNITY GROUPS IN PUJONKIDUL VILLAGE, PUJON DISTRICT, MALANG REGENCY, EAST JAVA - Ugik Romadi; Gunawan; Yeni Pramita (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to find the concept of how tourism awareness groups are able to develop agro-tourism through the social capital owned by Pujonkidul Village and how the Tourism Awareness Group is able to integrate all elements of society with low educational and human resource backgrounds and to produce more productive activities in realizing sustainable agro-tourism. Researchers used a qualitative method with a phenomenological approach. The results of this study indicate that the Sawah cafe is a vital organ in the development of agro-tourism in Pujonkidul. Sawah cafe is an attraction with the highest interest compared to other attractions. Social integration that occurs in all elements of society provides convenience in the process of developing agro-tourism, Community activeness in the tourism development process can support and uphold local culture, traditions, knowledge and skills, and create pride in community heritage and finally this research finds an applicable concept of how the Tourism-aware group is able to play a role in utilizing existing social capital to develop agro-tourism, which by integrating community capacity, community roles and stake holders, and community initiatives.